The A-ring reduction of 11-ketotestosterone is efficiently catalysed by AKR1D1 and SRD5A2 but not SRD5A1. Issue 202 (September 2020) - Barnard, Lise; Nikolaou, Nikolaos; Louw, Carla; Schiffer, Lina; Gibson, Hylton; Gilligan, Lorna C.; Gangitano, Elena; Snoep, Jacky; Arlt, Wiebke; Tomlinson, Jeremy W.; Storbeck, Karl-Heinz
Highlights: 11-ketotestosterone is efficiently 5β -reduced by AKR1D1. SRD5A2, but not SRD5A1 catalyses the 5α-reduction of 11-ketotestosterone. Metabolism of 11-ketotestosterone overlaps with cortisone metabolism. 11-ketoandrosterone is a urinary marker of 11-ketotestosterone. Abstract: Testosterone and its 5α-reduced form, 5α-dihydrotestosterone, were previously thought to represent the only active androgens in humans. However, recent studies have shown that the potent androgen, 11-ketotestosterone, derived from the adrenal androgen precursor, 11β-hydroxyandrostenedione, may in fact serve as the primary androgen in healthy women. Yet, despite recent renewed interest in these steroids, their downstream metabolism has remained undetermined. We therefore set out to investigate the metabolism of 11-ketotestosterone by characterising the 5α- or 5β-reduction commitment step. We show that inactivation of 11-ketotestosterone is predominantly driven by AKR1D1, which efficiently catalyses the 5β-reduction of 11-ketotestosterone, committing it to a metabolic pathway that terminates in 11-ketoetiocholanolone. We demonstrate that 5α-reduction of 11-ketotestosterone is catalysed by SRD5A2, but not SRD5A1, and terminates in 11-ketoandrosterone, but is only responsible for a minority of 11-ketotestosterone inactivation. However, as 11-ketoetiocholanolone is also generated by the metabolism of the glucocorticoid cortisone, 11-ketoandrosterone should be considered a more specific urinary marker of 11-ketotestosterone production.